Home blood pressure measurement and digital health: communication technologies create a new context. Issue 11 (November 2018) - Postel-Vinay, Nicolas; Bobrie, Guillaume; Savard, Sébastien; Persu, Alexandre; Amar, Laurence; Azizi, Michel; Parati, Gianfranco
Abstract : N/A: Ambulatory blood pressure (BP) monitoring is encouraged by all international guidelines for the management of hypertension. Home BP monitoring is the preferred method of the patients. Automated BP devices with remote data transmission have been repeatedly shown to be useful in improving hypertension control in the frame of clinical trials on telemedicine. Recently, new technologies have created a new context. Despite the important number of smartphone apps devoted to BP developed these last 10 years, only two BP monitoring apps refer to the European Society of Hypertension (ESH) Guidelines and have been published in peer-reviewed journals: Hy-Result and ESH CARE. At present, the absence of close collaboration between start-up engineers and healthcare professionals is a risk for patient safety. Therefore, health professionals must become actors in the so-called digital health revolution.